Photochemically assisted synthesis of phenacenes fluorinated at the terminal benzene rings and their electronic spectra - Ishii, Yuuki; Yamaji, Minoru; Tani, Fumito; Goto, Kenta; Kubozono, Yoshihiro; Okamoto, Hideki (Beilstein Journal of Organic Chemistry, 2025)
[n]Phenacenes ([n] = 5–7), octafluorinated at the terminal benzene rings (F8-phenacenes: F8PIC, F8FUL, and F87PHEN), were photochemically synthesized, and their electronic spectra were investigated to reveal the effects of the fluorination on the electronic features of phenacene molecules. F8-Phenacenes were conveniently synthesized by the Mallory photoreaction of the corresponding fluorinated diarylethenes as the key step. Upon fluorination on the phenacene cores, the absorption and fluorescence bands of the F8-phenacenes in CHCl3 systematically red-shifted by ca. 3–5 nm compared to those of the corresponding parent phenacenes. The vibrational progressions of the absorption and fluorescence bands were little affected by the fluorination in the solution phase. In the solid state, the absorption band of F8-phenacenes appeared in the similar wavelength region for the corresponding parent phenacenes whereas their fluorescence bands markedly red-shifted and broadened. These observations suggest that the intermolecular interactions of excited-state F8-phenacene molecules are significantly different from those of the corresponding parent molecules, most likely due to different crystalline packing motifs.
Keywords: fluorescence; fluorinated aromatics; phenacene; photoreaction